Editorial 9.3 - Peseta, Tai (Journal of University Teaching and Learning Practice, 2012)
This Special Edition of JUTLP is unique in that it examines a single university's approach to curriculum reform, providing insights from many of the people who were engaged in the process.At La Trobe University in Australia the mechanism for engaging in discussions at a university level has been encapsulated in an institutional strategy known as Design for Learning (DfL) (La Trobe University 2009). From 2007, former Deputy Vice-Chancellor (Academic) Belinda Probert and former Pro Vice-Chancellor (Curriculum and Academic Planning) Tom Angelo, led an exciting and edgy curriculum change initiative intended to build on La Trobe’s learning and teaching strengths, while simultaneously building a systems focus for ensuring curriculum quality and renewal. The blueprint for the DfL described its principles thus: “ … highlight[ing] breadth of choice, equity, flexibility (options), learning centred-ness, research and evidence based decision making, a systems focus (rather than making individuals responsible for things they do not control), and support (resources)” (La Trobe University 2009, p. 7).With goodwill, energy and a profound sense that ‘something needed to be done’, in the early years of the DfL, the university was alive with fresh talk of curriculum, teaching and student learning galvanised by new leadership, a commitment to evidence-based change, resources to fund curriculum innovation, together with the promise of reward and recognition. Imagine the scene: committees and communities spring up to think together about complex pedagogical issues, spirited discussion takes place, departments and faculties share resources and good practices, new staff are brought on board with responsibility to make things happen.The 7 papers represented here describe both large and small curriculum change initiatives – some funded by the university and others done out of love, curiosity and interest.